Ovarian peroxidase and sialic acid activities during the reproductive cycle of Heteropneustes fossilis (Bloch) - Ghosh, Subho; Gupta, Santasri Sen; Ghosh, Ashok (Indian Journal of Fisheries, 2011)
Peroxidase enzyme and sialic acid are spectrophotometrically estimated from the ovaries of the Indian catfish (Heteropneustes fossilis) during the annual ovarian cycle. Three phases of the reproductive cycle identified are, last part of pre-spawning, spawning and first part of post-spawning. It becomes evident that peroxidase is the "marker enzyme" during the spawning period of H. fossilis